MISKONSEPSI SISWA PADA MATERI PERTIDAKSAMAAN LINIER SATU VARIABEL DI SMK-SMTI PONTIANAK - Linda Rahayu; Halini Halini; Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractIn this research, Misconception is an inaccurate definition or comprehension about a concept and the use of a concept that is not in accordance with the concept that has been negotiated scientifically by an expert from that field, also an inability to associate the initial concept with the next one correctly in linear inequality of one variable. The purpose of this research is to discover student’s misconceptions in the linear inequality of one variable and the cause of it in grade X SMK-SMTI Pontianak. The tools used to detecting student’s misconceptions in this subject are four-tier diagnostic tests while the form of the research is a case study with a descriptive method. The techniques to gather the data in this research are test (written test) and non-test (interview). The result from misconception description analysis that has been done by students found that misconception happened in translation, concept, systematic, and calculation. Based on the form of the misconception that students have, the most is a misconception in the concept. The causes of student’s misconceptions are preconception or an initial concept, student’s associative thinking, incorrect reasoning, inaccurate intuition, student’s capability and the lack of students' interest in learning. Some causes of misconception showed that preconception or initial concept is the misconception that happened most to the students. Keywords: Misconception, Four-Tier Diagnostic Test, linear inequality of one variable